Label-free designed nanomaterials enrichment and separation techniques for phosphoproteomics based on mass spectrometry - Rejeeth, Chandrababu; Sharma, Alok (Frontiers in Nanotechnology, 2022)
The surface chemical characteristics of nanomaterials have a substantial impact on the affinity probe used to enrich proteins and peptides for MALDI-MS analysis of a real human sample. Detecting phosphoproteins involved in signalling is always difficult, even with recent developments in mass spectrometry, because protein phosphorylation is often temporary from complicated mixtures. This review summarizes current research on the successful enrichment of various intriguing glycoproteins and glycol peptides using surface affinity materials with distinctive qualities such as low cost, excellent structural stability, diversity, and multifunction. As a consequence, this review will provide a quick overview of the scholars from various backgrounds who are working in this intriguing interdisciplinary field. Label-free cancer biomarkers and other diseases will benefit from future challenges.